COMPOUNDS OF NITROGEN AND PHOSPHORUS IN WATER BODIES OF THE KAZAKHSTAN PART OF THE IRTYSH RIVER BASIN (Eurasian Journal of Ecology, 2024)
We present materials from our research to study the distribution of various forms of mineral nitrogen and phosphorus in the Irtysh River basin in the summer of 2023. It has been established that the content of mineral forms of nitrogen and their ratios are not the same in the water of rivers and lakes. In the water of the river's tributaries. The Irtysh River was dominated by nitrate ions (from 0.039 to 1.033 mgN/dm3), with a maximum in the right-bank tributaries. The nitrite and ammonium ions share accounted for 2.7, 32.7 and 15.3, 38.3% of the total nitrogen, respectively. The share of nitrates in the Black Irtysh River averaged 59% of the amount of nitrogen. Downstream, within the Pavlodar region, nitrates were more often absent, and the proportion of ammonium nitrogen increased. Mineral soluble phosphorus (phosphate ions) was found in the water of all surveyed areas of the basin in insignificant concentrations (0.015 - 0.130 mg/dm3) due to the low solubility of its compounds and intensive absorption by hydrobionts. From the upper to the lower sections of the Irtysh there was a slight increase in the concentration of nitrogen and phosphorus compounds, as a result of the influence of the anthropogenic factor.Key words: nutrients, nitrites, nitrates, ammonium ion, phosphates, natural waters, hydrochemistry, maximum permissible concentration, pollution, ecology.